MEASURING AND EVALUATING JAPANESE PEOPLE'S NERVOUSNESS IN SPEAKING ENGLISH - Shudong WANG; Michael HIGGINS; Makoto ICHIKAWA; Shengfu LU (KANSEI Engineering International, 2005)
Abstract:In this study, we measured and evaluated the nervousness of Japanese native speakers in speaking English with non-Japanese from different countries. Questionnaires were given to the participants, and an experiment measuring the participants'physiological responses of nervousness was conducted. The experimental data was observed and analyzed by paired t-tests and fuzzy sets mathematical theory. We discovered that most of the Japanese participants(subjects), in spite of their English level, feel more nervous when talking to“typical”Caucasian native English speakers, than when talking to Chinese or Koreans, with whom they share similar East Asian physiological and psychological characteristics. This shows that East Asian people who have a good command of English can be regarded as viable English teaching resources in Japan, as their presence in the class decreases nervousness among the students.